Successive applications of gibberellic acid to reduce flowering of ’Montenegrina’ mandarin in alternate bearing - Griebeler, Sabrina Raquel; Gonzatto, Mateus Pereira; Böettcher, Gerson Nestor; Schneider, Leonardo André; Sulzbach, Manuela; Gargioni, Eduarda Dorigatti; Schwarz, Sergio Francisco (Pesquisa Agropecuaria Brasileira, 2021)
The objective of this work was to evaluate the number of successive applications of gibberellic acid (GA3), during the autumn-winter period, for its effect on the reduction of flowering, in the subsequent spring after periods of low fruit load (off-year), in 'Montenegrina' mandarin trees (Citrus deliciosa). Sequential applications at 40 mg L-1 GA3 were tested from one to four times, at 21-day intervals, beginning in the end of May. The experiment was carried out in a randomized complete block design, with four treatments and a control, four replicates, and one plant per experimental unit. Flowering, sprouting, types of shoots, fruit set, and fruit diameter were evaluated. The fruit set increases exponentially with the reduction of flowering intensity. The use of GA3 in two, three, or four sequential applications, from May to June, May to July, and from May to August, at 21-day intervals, reduces the intensity of flowering and sprouting of alternate bearing plants in the subsequent spring, increasing mixed shoots and reducing floral shoots. The use of four sequential applications of 40 mg L-1 GA3 promotes a great increase in the frequency of single flower terminal leafy shoots and favors the increase of fruit fixation and size.